Injury prevention - Marks, S. (FINA World Sports Medicine Congress, 18, 2016)
Dr. Saul Marks, University of Toronto (CAN), talks about " Injury Prevention: Knowledge Translation for Athletes and Coaches" at the FINA World Sports Medicine Congress 2016.(17:50 min).